PENGAWASAN DINAS PERINDUSTRAN DAN PERDAGANGAN DALAM PENGELOLAAN PASAR BAWAH DI KOTA PEKANBARU TAHUN 2022-2023 - Akhasa, Annas; Hadi, Sofyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Department of Industry and Trade is an executive element of the Regional Government in the field of industry and trade. One of the tasks of the Industrial and Trade Department of the City of Pekanbaru is to monitor the activities carried out by private entities in the management of the Lower Market. The problems in this study are not optimum processes of supervision carried on by the industrial and trade department of the city of pekanbaru, thus decreasing the attractiveness and competitiveness of the lower market. The purpose of this research is to look at the monitoring process carried out by the Industrial and Trade Department of Pekanbaru City in the year 2022-2023. This research uses descriptive qualitative research methods with primary data sources and secondary data. Data collection techniques are interview techniques and documentation techniques. Data analysis techniques are Data Reduction, Data Presentation, and Conclusion Drawing. The results of this study are the surveillance carried out by the Industrial and Trade Department of Pekanbaru City in the management of the market under 2022-2023 has basically been implemented in accordance with the existing rules. But in that year there was a transition period, in which the current managers in the lower markets were replaced, so that the monitoring process was not working significantly. Besides, there are also obstacles among them, polemics between the lower market trader with the new manager as well as the process of transferring the trader from the bottom market to the TPS lower market. Keywords: Government Oversight, Implementation Standards, Correctional Action